2018
DOI: 10.1016/s1473-3099(18)30018-5
|View full text |Cite
|
Sign up to set email alerts
|

Re-emergence of Aedes aegypti in Egypt

Abstract: spondylodiscitis caused by a fully sensitive M tuberculosis isolate. 4 In our Clinical Picture, 1 the patient's improvement started 10 days after the beginning of treatment, followed by a complete clinical recovery and return of systemic inflammatory markers to normal concentrations. 2 months after treatment in hospital, the follow-up MRI showed significant regression of the epidural abscess, which would have been highly improbable in tuberculous spondylodiscitis. Therefore, in our opinion, the results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 2 publications
2
24
0
Order By: Relevance
“…albopictus , respectively. The presence of these species were recently confirmed via active surveillance of these two vectors in the same regions anticipated by our models [41–44].…”
Section: Discussionsupporting
confidence: 76%
“…albopictus , respectively. The presence of these species were recently confirmed via active surveillance of these two vectors in the same regions anticipated by our models [41–44].…”
Section: Discussionsupporting
confidence: 76%
“…On the Arabian Peninsula, DENV has been endemic in the Kingdom of Saudi Arabia since 2004 (Alghazali et al, 2019), and is very likely to be considered endemic in Yemen where vector control has diminished over the last 4 years due to the war (Humphrey et al, 2019).A study of the seroprevalence of dengue virus in Qatar found that 7/200 (3.5%) of Qatari nationals were seropositive, but is not known if these had a travel history to a DENV-endemic area (Chinikar et al, 2013). DENV is also endemic in Iran as demonstrated by a retrospective serosurvey study in 2012 (Abozeid et al, 2018). A. aegypti is present in Egypt, where autochthonous DENV cases have been confirmed recently (Dickens et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CHIKV antibodies have also been reported from Egypt in the 1970s and 80s, and the country has experienced recent DENV outbreaks and is known to harbor Ae . aegypti [2, 72]. However, to our knowledge, no CHIKV outbreaks have yet been reported in Egypt.…”
Section: Discussionmentioning
confidence: 99%